Product-Influencer Fit terhadap Attitude Toward Influencer, Influencer Credibility, Attitude Toward Product dan Dampaknya pada Purchase Intention Produk Whitelab - Nadia Ramadhani Nugroho Putri; Tanti Handriana (Journal of Management and Bussines (JOMB), 2024)
This research aims to investigate the influence of product-influencer fit on attitudes towards influencers, influencer credibility, attitudes towards products, and their impact on purchase intentions. We also wanted to see the compatibility between the Whitelab Cera-Mug Barrier Moisturizing Gel product and the influencer Bintang Emon. A quantitative approach was used in this research, using SEM-PLS analysis techniques and the SmartPLS 3.0 application to test the data. Respondents consisted of Bintang Emon followers who were aware of the Whitelab Cera-Mug Barrier Moisturizing Gel product promoted by the influencer, but had never purchased the product. The number of respondents was 198 people with age criteria over 18 years. The research results show that there is a positive influence of product-influencer fit on attitudes towards influencers, influencer credibility, and attitudes towards products. Apart from that, the credibility of the influencer also influences attitudes towards the influencer and attitudes towards the product. However, no significant influence was found from product-influencer fit, influencer credibility, and attitude towards the influencer on purchase intentions. Conclusion, this research highlights the importance of the match between the product and the influencer in influencing the influencer's attitudes and credibility as well as attitudes towards the product. However, to increase purchase intent, other factors may need to be considered besides product-influencer fit, influencer credibility, and attitudes toward the influencer. Keywords: Influencer Credibility, Purchase Intention, Product-Influencer Fit, Attitude Toward the Product